Toward a Professional Development Model for Writing as a Digital, Participatory Process. Issue 1 (9th January 2020) - Howell, Emily; Perez, Sara; Abraham, W. Todd
ABSTRACT: In this formative experiment, the authors focused on developing professional development for upper elementary school teachers and investigating how it was integrated into teachers' instruction to improve their ability to make writing a more digital, participatory process. Theoretical perspectives pertaining to technology use in education specify that this instruction should emphasize students creating rather than consuming information from media sources and that this creation process should be social. However, recent research of preadolescents has shown that although these students are using technology more in schools, they are often using technology to consume rather than create information. Further, literacy teachers, in particular, have identified barriers to integrating technology effectively into their curriculum. Thus, there is a critical need for professional development that helps teachers more effectively integrate technology into their classrooms. The objective of this study was to develop a professional development model that helps teachers engage students in writing as both a digital process and a social process. The essential elements studied in this model include the following: (a) sustained professional development, including the gradual release of teacher inquiry; (b) writing as a social practice; and (c) the use of digital tools to engage students in writing. Using both qualitative and quantitative methods, the authors studied the implementation of this professional development model in a summer institute and in teacher classrooms.